ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS V SD DALAM MENYELESAIKAN SOAL MATERI BILANGAN CACAH DITINJAU DARI SELF EFFICACY - Ruslan, Liliani; Rien Anitra; Rini Setyowati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to: 1) describe the mathematical problem solving abilities of fifth grade students who have high self-efficacy in solving whole number problems. 2) describe the mathematical problem solving abilities of fifth grade students who have moderate self-efficacy in solving whole number material problems. 3) describe the mathematical problem solving abilities of fifth grade students who have low self-efficacy in solving whole number material problems. The research used is qualitative research with descriptive qualitative research type. The subjects in this research were class V students at SDN 4 Singkawang. The research object is the mathematical problem solving ability of class V students in solving whole number material problems in terms of self-efficacy. The data collection techniques used in this research were interviews, giving mathematical problem solving ability tests, self-efficacy questionnaires and documentation. The research results show that: 1) Mathematical problem solving ability is being viewed from high self-efficacy. 3 students have an average score of 2 with a percentage of 48.23%. It can be seen from this score that students are able to carry out mathematical problem solving, 2) Ability Mathematical problem solving is being reviewed from self efficacy, while 14 students have an average score of 3 with a percentage of 77.08%. It can be seen from this score that students can carry out mathematical problem solving well but are often mistaken and not careful in carrying out problem solving plans. . and 3) Mathematical problem solving ability is being viewed from low self efficacy. 3 students have an average score of 2 with a percentage of 22.91%. It can be seen from this score that students are less able to carry out mathematical problem solving well. Keywords: Mathematical Problem Solving Ability,Whole Numbers, Self Efficacy.